STUDY OF FUNCTIONAL AND RADIOLOGICAL OUTCOMES OF OPEN REDUCTION AND INTERNAL FIXATION OF PROXIMAL HUMERUS FRACTURES WITH PROXIMAL HUMERUS LOCKING PLATE - GAMI, DHAWAL; BANDE, PRAVIN; WAJEKAR, SAGAR (International Journal of Current Pharmaceutical Research, 2024)
Objective: Proximal humeral fractures, representing approximately 5% of all fractures, intricately challenge orthopaedic management, particularly in the geriatric demographic. Displaced variants, frequently encountered in the elderly, prompt surgical intervention to mitigate notable morbidity. The introduction of angular stable proximal humerus locking plates heralds a pivotal shift, purveying biomechanical robustness in osteoporotic contexts. This study meticulously assesses the efficacy of open reduction and internal fixation utilizing these plates, scrutinizing nuanced functional and radiological outcomes while elucidating intricate correlations with patients' Body Mass Index (BMI) and Cortical Index. Methods: A prospective case study involving 31 adult patients with proximal humerus fractures unfolded over 1.5 y within the bastions of the Department of Orthopaedics at BARC Hospital. Inclusion criteria encompassed specific fracture morphologies, while exclusion criteria diligently precluded medically infirm subjects and isolated tuberosity fractures. Radiographic scrutiny encompassed parameters such as cortical index, fracture classification, neck-shaft angle, GT to AS distance, and medial hinge reduction. Functional assessments, including QuickDASH and Constant-Murley scoring, were conducted postoperatively at 3 and 6 mo. Correlation analyses interfacing with BMI and cortical index engendered a profound understanding. Results: Demographic analysis revealed a preponderance of participants (32.3%) within the 61-70 age bracket, with 54.8% manifesting Neer 2-part fractures. The cohort exhibited an average BMI of 26.27 (SD = 4.29), coupled with a Cortical Index averaging 0.216 (SD = 0.012). Significantly improved QuickDASH scores, dwindling from 25.54±6.74 at 3 mo to 13.16±8.57 at 6 mo (p<0.0001), underscored noteworthy clinical advancement. Complications, while relatively infrequent, manifested in 6.5% as screw penetration and 9.7% as superficial infection. Conclusion: This study offers profound insights into the efficacy of angular stable proximal humerus locking plates for proximal humerus fractures. The discerned stability in anatomical metrics, coupled with substantial functional amelioration and a judiciously low complication milieu, emphatically underscores the procedural effectiveness. Correlation analyses unmask intricate associations with BMI and cortical index. Despite auspicious outcomes, ongoing research imperatively seeks refinement of understanding and the delineation of prophylactic measures for complications.